Transformative research and capacity building in the education sector to protect livelihoods and biodiversity in Costa Rica - Gorris, Philipp (2023)
Osnabrück University and Universidad Técnica Nacional develop inter- and transdisciplinary approaches in research and education to restore and protect biodiversity. In Costa Rica, many persistent social-ecological conflicts can be observed. The case of the Gulf of Nicoya offers a suitable testing ground for the approaches developed as part of this partnership. This article introduces the project’s focus on the relationship between cultural, economic and political aspects related to conservation, sustainable land use and community development. Currently, the project conducts research on social-ecological conflicts in the Costa Rican pineapple production and its impacts on biological diversity across the land-sea interface. The inter- and transdisciplinary project approach to research and education generates tangible knowledge among researchers, students, and non-scientific local actors.